GA4GH: International policies and standards for data sharing across genomic research and healthcare - Heidi L. Rehm; Angela J.H. Page; Lindsay Smith; Jeremy B. Adams; Gil Alterovitz; Lawrence J. Babb; Maxmillian P. Barkley; Michael Baudis; Michael J.S. Beauvais; Tim Beck; Jacques S. Beckmann; Sergi Beltran; et al. (Cell Genomics, 2021)
Summary: The Global Alliance for Genomics and Health (GA4GH) aims to accelerate biomedical advances by enabling the responsible sharing of clinical and genomic data through both harmonized data aggregation and federated approaches. The decreasing cost of genomic sequencing (along with other genome-wide molecular assays) and increasing evidence of its clinical utility will soon drive the generation of sequence data from tens of millions of humans, with increasing levels of diversity. In this perspective, we present the GA4GH strategies for addressing the major challenges of this data revolution. We describe the GA4GH organization, which is fueled by the development efforts of eight Work Streams and informed by the needs of 24 Driver Projects and other key stakeholders. We present the GA4GH suite of secure, interoperable technical standards and policy frameworks and review the current status of standards, their relevance to key domains of research and clinical care, and future plans of GA4GH. Broad international participation in building, adopting, and deploying GA4GH standards and frameworks will catalyze an unprecedented effort in data sharing that will be critical to advancing genomic medicine and ensuring that all populations can access its benefits.